شیكردنه‌وه‌ی جوگرافی بۆ خواست وخستنه‌ڕووی گۆشتی ماسی له‌ هه‌رێمی كوردستان له‌ نێوان ساڵانی (2010-2022) - تالیب, پ. د. جه‌زا تۆفیق; مسته‌فا, م.ی. ڕۆسته‌م جه‌بار (Sulaimani Journal for Humanities, 2023)
Along with other meat categories, fish meat is considered as one of the most significant kind of meat. In Kurdistan Region. As far as the human population has increased, the order for fish meat also increased. It has been an important dietary source of protien and other nutrients throughout the history. As well as, as has been said, its other advantages as a healthy food for instance; it reserves people from such illnesses. In Kurdistan, each person has (6) Kg of fish per year. Since Kurdistan is not an opened sea cost area hence it is somehow difficult to achieve enough fish meat, so that a shortage can easily be noticed. In order to solve this issue, several aquacultural projects has been constructed by farmers to produce fish according to fill the needs in Kurdistn.These projects can not fulfil Kurdish people´s need so that it has been imported from other countries that costs a large budget. However, importing it from outside causes to waste a serious threat to national food security in the follwoing years but (%90) percent of meat fish are imported.
Keywords: supply; demand; fish gap; Kurdistan Region